The - O'Sullivan, Janet (Oxford University Press, 2008)
The Core Text Series takes the reader straight to the heart of the subject, providing a reliable and invaluable guide for students of law at all levels. Written by leading academics and renowned for their clarity, these concise texts explain the intellectual challenges of each area of the law